Uwagi wstępne o niemieckiej leksyce wojskowej okresu międzywojennego (na podstawie "Słownika niemiecko-rosyjskiego" A. F. Nesslera) = Preliminary remarks on German military lexis of the interwar period (a study based on A.F. Nessler`s "German-Russian Dictionary") - Sobczak, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present paper demonstrates a preliminary study of German military lexis of the interwar period. It has been established that even though scientists have already undertaken such research, they have so far based it on their own observations, accounts of soldiers and military song lyrics. None of the works have made use of dictionary sources.
Keywords: Nessler, Aleksej Fedorovič; niemiecka leksyka wojskowa; 1918-1939; słownik rosyjsko-niemiecki; zapożyczenie; German military lexis; interwar period; dictionary; loan-words